Tracking the Dynamic Evolution of Participant Salience in a Discussion - Awadallah, Ahmed; Fader, Anthony; Crespin, Michael H.; Quinn, Kevin M.; Monroe, Burt L.; Colaresi, Michael; Radev, Dragomir R. (Association for Computational Linguistics, 2008)
We introduce a technique for analyzing the temporal evolution of the salience of participants in a discussion. Our method can dynamically track how the relative importance of speakers evolve over time using graph based techniques. Speaker salience is computed based on the eigenvector centrality in a graph representation of participants in a discussion. Two participants in a discussion are linked with an edge if they use similar rhetoric. The method is dynamic in the sense that the graph evolves over time to capture the evolution inherent to the participants salience. We used our method to track the salience of members of the US Senate using data from the US Congressional Record. Our analysis investigated how the salience of speakers changes over time. Our results show that the scores can capture speaker centrality in topics as well as events that result in change of salience or influence among different participants.